Absence of MERS-CoV antibodies in feral camels in Australia: Implications for the pathogen's origin and spread - Crameri, G.; Durr, P.; Barr, J.; Yu, M.; Graham, K.; Williams, O.; Kayali, G.; Smith, D.; Peiris, M.; Mackenzie, John; Wang, L. (2015)
Middle East respiratory syndrome coronavirus (MERS-CoV) infections continue to be a serious emerging disease problem internationally with well over 1000 cases and a major outbreak outside of the Middle East region. While the hypothesis that dromedary camels are the likely major source of MERS-CoV infection in humans is gaining acceptance, conjecture continues over the original natural reservoir host(s) and specifically the role of bats in the emergence of the virus. Dromedary camels were imported to Australia, principally between 1880 and 1907 and have since become a large feral population inhabiting extensive parts of the continent. Here we report that during a focussed surveillance study, no serological evidence was found for the presence of MERS-CoV in the camels in the Australian population. This finding presents various hypotheses about the timing of the emergence and spread of MERS-CoV throughout populations of camels in Africa and Asia, which can be partially resolved by testing sera from camels from the original source region, which we have inferred was mainly northwestern Pakistan. In addition, we identify bat species which overlap (or neighbour) the range of the Australian camel population with a higher likelihood of carrying CoVs of the same lineage as MERS-CoV. Both of these proposed follow-on studies are examples of "proactive surveillance", a concept that has particular relevance to a One Health approach to emerging zoonotic diseases with a complex epidemiology and aetiology.